Newly-diagnosed rheumatoid arthritis patients have elevated levels of plasma extracellular vesicles with protein cargo altered towards inflammatory processes - Anne Rydland; Fatima Heinicke; Tuula A. Nyman; Anne-Marie Siebke Trøseid; Siri T. Flåm; Maria Stensland; Johanna Gehin; Joakim Eikeland; Reidun Øvstebø; Maria Dahl Mjaavatten; Benedicte A. Lie (Scientific Reports)
Abstract Extracellular vesicles (EVs) are implicated in rheumatoid arthritis (RA) but have mainly been assessed in RA patients taking disease modifying anti-rheumatic drugs. EVs are nanoparticles important in cell-cell communication and their molecular cargo are biomarker candidates. We characterized the protein profiles of EVs from blood plasma from newly diagnosed, treatment naïve RA patients (N = 32) and compared them to healthy controls (N = 20), by size exclusion chromatography-based EV enrichment coupled with high-resolution quantitative proteomics. The RA patients had higher EV concentration and larger EVs than controls. A total of 682 EV proteins were reliably quantified, and the overall profiles were distinctly different between patients and controls. Specifically, 26 proteins were significantly upregulated and 31 downregulated in RA patients, with several proteins acting in inflammatory networks and with immunologically important upstream regulators. The RA associated EVs appear, based on the tissue expression of their cargo proteins, to originate mainly from hepatocytes or immune cells, like neutrophils. Interestingly, the strongest RA associated EV proteins were inflammatory molecules, like SAA1 and S100A9, already suggested as biomarkers in RA. Furthermore, the RA associated EV proteins were generally not correlated with total serum protein levels, stressing the importance of EV transport of inflammatory proteins in RA pathogenesis.